SPIP Maturity, APIP Capabilities, Performance Accountability, and Organizational Integrity as Audit Opinion Predictors - Trisni Clara Napitupulu; Henryanto Wijaya (LP2M IAIN Palopo, 2026)
This study aims to examine the role of Government Internal Control System (SPIP) maturity, Government Internal Supervisory Apparatus (APIP) capability, performance accountability, and organizational integrity as predictors of audit opinions in Indonesian local governments. Based on agency theory, these governance mechanisms are expected to reduce information asymmetry and improve the quality of financial reporting, thereby increasing the likelihood of obtaining an unqualified audit opinion. This study employed a quantitative approach with a predictive research design. The sample consisted of 510 provincial, regency, and municipal governments in Indonesia during the 2022–2024 period selected using purposive sampling. Secondary data were collected from publications issued by the Audit Board of Indonesia (BPK), the Financial and Development Supervisory Agency (BPKP), the Ministry of Administrative and Bureaucratic Reform, and the Corruption Eradication Commission (KPK). Logistic regression analysis was applied to examine the predictive ability of the independent variables on audit opinions classified as Unqualified Opinion (WTP) and Non-WTP. The results indicate that the logistic regression model is fit for prediction purposes, as evidenced by the Hosmer–Lemeshow significance value of 0.122 and Nagelkerke R Square of 0.208. The findings reveal that SPIP maturity and organizational integrity are significant predictors of audit opinions, while APIP capability and performance accountability are not significant predictors. Higher levels of SPIP maturity and organizational integrity increase the likelihood of local governments obtaining an unqualified audit opinion. These findings imply that strengthening internal control systems and fostering organizational integrity are essential strategies for improving audit outcomes and public sector governance. Future studies are encouraged to incorporate additional governance and institutional factors to enhance the explanatory power of audit opinion prediction models.